2006
DOI: 10.1007/s10461-006-9151-1
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Behavioral Interventions to Reduce HIV Risk Behaviors of Hispanics in the United States and Puerto Rico

Abstract: This systematic review examines the overall efficacy of HIV behavioral interventions designed to reduce HIV risk behaviors or incident sexually transmitted diseases (STDs) among Hispanics residing in the United States or Puerto Rico. Data from 20 randomized and nonrandomized trials (N = 6,173 participants) available through January 2006 were included in this review. Interventions successfully reduced the odds of unprotected sex and number of sex partners, increased the odds of condom use, and decreased the odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
148
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 142 publications
(153 citation statements)
references
References 85 publications
5
148
0
Order By: Relevance
“…12 Herbst's meta-analysis of 20 interventions among Latinos found significantly greater efficacy associated with interventions that included problem-solving skills coaching, that did not use peers, and that addressed the influences of machismo. 13 We extend the results of previous reviews by including a number of articles published in the last few years; the 2007 review by Crepaz et al only includes articles published through June 2005, 10 while our review includes 18 articles published since, including six interventions targeting adolescents, four targeting STD clinic patients, and the only two interventions identified in our review targeting high-risk men. Also, 10 of the studies in our review describe interventions not tested in random-ized control trials.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…12 Herbst's meta-analysis of 20 interventions among Latinos found significantly greater efficacy associated with interventions that included problem-solving skills coaching, that did not use peers, and that addressed the influences of machismo. 13 We extend the results of previous reviews by including a number of articles published in the last few years; the 2007 review by Crepaz et al only includes articles published through June 2005, 10 while our review includes 18 articles published since, including six interventions targeting adolescents, four targeting STD clinic patients, and the only two interventions identified in our review targeting high-risk men. Also, 10 of the studies in our review describe interventions not tested in random-ized control trials.…”
Section: Discussionmentioning
confidence: 91%
“…13,14 However, none of the studies included in these prior reviews directly manipulated the number of sessions as part of the trial. We identified two studies that directly examined number of sessions; one found no difference in intervention effects across groups assigned to two versus four sessions, 37 and the other found that patients randomized to an eight-session intervention had significantly better outcomes than zero-session controls, while those assigned a four-session intervention did not.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations